Physiotherapist inter‐rater reliability of the Haemophilia Early Arthropathy Detection with Ultrasound protocol. Issue 3 (1st March 2018) - Stephensen, D.; Classey, S.; Harbidge, H.; Patel, V.; Taylor, S.; Wells, A.
Abstract : Introduction: Prevention of arthropathy is the major goal of haemophilia treatment, and early detection of the first signs of joint damage is important so that prevention strategies can be initiated to limit physical disability and improve quality of life. Aim: The aim of this study was to determine the inter‐rater repeatability of the HEAD‐US protocol when performed by haemophilia physiotherapists. Methods: Sixty‐three joints (21 elbows, 21 knees and 21 ankles) were examined in 21 patients (mean age; 29.14 ± 10.09 years) according to the HEAD‐US protocol by four of six physiotherapists blinded to clinical information. Inter‐rater repeatability was evaluated by comparing the concordance of scores between the different clinicians using weighted Kappa (κw ) statistics and 95% confidence intervals. Results: Substantial agreement was found when evaluating synovial hypertrophy (κw  = 0.69), articular cartilage (κw  = 0.60) and bone (κw  = 0.74). Near perfect repeatability (κw  > 0.80) was found when scoring synovitis profiles of the elbow joint and bone profiles of the knee joint. Repeatability was moderate for scoring synovitis and articular cartilage profiles of the ankle joint. A moderate correlation between HEAD‐US and HJHS was found for the elbow and ankle joint and a strong correlation for the knee joint. Discordance between clinical and ultrasound examination was 19.30%. Conclusion: Overall, we found repeatability of the HEAD‐US protocol was good when performed by physiotherapists, and our results support the emerging view that US imaging complements the physical examination when screening and monitoring joint health of people with haemophilia at the point of care.